2004
DOI: 10.1128/aem.70.12.7426-7435.2004
|View full text |Cite
|
Sign up to set email alerts
|

Shear Rate Moderates Community Diversity in Freshwater Biofilms

Abstract: The development of freshwater multispecies biofilms at solid-liquid interfaces occurs both in quiescent waters and under conditions of high shear rates. However, the influence of hydrodynamic shear rates on bacterial biofilm diversity is poorly understood. We hypothesized that different shear rates would significantly influence biofilm diversity and alter the relative proportions of coaggregating and autoaggregating community isolates. In order to study this hypothesis, freshwater biofilms were developed at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
90
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 53 publications
10
90
1
Order By: Relevance
“…Some Acidovorax species isolated from freshwater biofilm communities showed strong autoaggregating abilities, and possessed high whole-cell hydrophobicity which can enhance the autoaggregation interactions. And it is suggested that aggregating abilities and whole-cell hydrophobicity are important for colonization and biofilm development in flowing environments (Rickard et al, 2004). Biofilm formation in oligotrophic drinking water environments also could be viewed as a successional process in structure and species compositions (Martiny et al, 2003).…”
Section: Bacterial Communitiesmentioning
confidence: 99%
“…Some Acidovorax species isolated from freshwater biofilm communities showed strong autoaggregating abilities, and possessed high whole-cell hydrophobicity which can enhance the autoaggregation interactions. And it is suggested that aggregating abilities and whole-cell hydrophobicity are important for colonization and biofilm development in flowing environments (Rickard et al, 2004). Biofilm formation in oligotrophic drinking water environments also could be viewed as a successional process in structure and species compositions (Martiny et al, 2003).…”
Section: Bacterial Communitiesmentioning
confidence: 99%
“…Some strains that were isolated on R2A agar (Reasoner & Geldreich, 1985) at the high velocities possessed unusual morphological and biochemical characteristics. In particular, strain MBRG1.5 T possessed a low partial 16S rRNA gene sequence identity (92?7 %) when compared with sequences from species with validly published names in the EMBL database (Rickard et al, 2004). In this study, strain MBRG1.5…”
mentioning
confidence: 98%
“…A recent study on the influence of water velocity on the community diversity of potable water biofilms demonstrated that the taxonomic diversity of biofilms developed at high velocities was much lower than that of biofilms developed under conditions of minimal velocity (Rickard et al, 2004). Some strains that were isolated on R2A agar (Reasoner & Geldreich, 1985) at the high velocities possessed unusual morphological and biochemical characteristics.…”
mentioning
confidence: 99%
“…The ability to coaggregate and autoaggregate have been found to enhance bacterial attachment, with a larger proportion of biofilm strains being able to coaggregate and autoaggregate compared to their planktonic counterparts (Rickard et al, 2004). Autoaggregation is a "selfish" mechanism whereby a strain within the biofilm will express polymers to enhance the integration of genetically identical strains (Rickard et al, 2003a) and may thus enhance the development of freshwater biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Autoaggregation is a "selfish" mechanism whereby a strain within the biofilm will express polymers to enhance the integration of genetically identical strains (Rickard et al, 2003a) and may thus enhance the development of freshwater biofilms. Autoaggregation interactions are enhanced by increased hydrophobicity and tend to be stronger than coaggregation (Rickard et al, 2004). Autoaggregation can be highly specific and is typically mediated by interactions between "adhesins" or specific carbohydrate-binding proteins (lectins) found on one cell and complementary saccharide "receptors" borne on another (Rickard et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%